Investigation of the relationship between different Candida species and some risk factors affecting the incidence of Vulvovaginal Candidiasis - Seyedeh Sedigheh Hosseini; Ezzatallah Ghaemi; Farhad Niknejad; Hamidreza Joshaghani; Mina Rabiee; Fahimeh Azadi; Toktam Sharafi; Naemeh Javid; Mahboobeh Kabir; Saba Modi; Farideh Jafari; Zahra Kamizi (Mashhad University of Medical Sciences, 2019)
Introduction: Vulvovaginal candidiasis (VVC) is a yeast infection and is one of the most common causes of women's referral to the physician. The aim of this study was to investigate the relationship between different Candida species and some risk factors affecting the incidence of vulvovaginal candidiasis. Methods: This descriptive study was conducted during 2016-2018 on 404 samples of vaginal discharge with clinical symptoms of vulvovaginitis in Sayyad Shirazi Hospital as well as Medical and Obstetric Clinics in Gorgan for two years. Vaginal secretions were tested directly on CHROMagar Candida medium and 280 patients with Candidiasis were identified using RFLP-PCR. The demographic information and individual fertility data were collected using a questionnaire. Subsequently, the data were analyzed in SPSS software (version. 22) through the Chi-square and Fisher's exact tests. P-value less than 0.05 was considered statistically significant. Results: According to the results, 62 (22%) patients had recurrent vulvovaginal; moreover, the incidence of the VVC correlated significantly with the age group of 26-35 years, the incidence of underlying diseases, pregnancy, and the use of contraceptive drugs, such as  LD, metronidazole, and fluconazole (P<0.05). However, no significant relationship was found between other symptoms (P>0.05). The most commonly identified species regarding the risk factors of vulvovaginal Candidiasis was Candida albicans. Conclusion: Awareness on the type of yeast, the type of effective antifungal drugs, and effective risk factors, such as broad and long-term use of antibiotics contraceptives, including LD, and some underlying factors can pave the way on the prevalence of the disease and the factors affecting the incidence of vulvovaginal candidiasis for medical specialists and health authorities.